A Study of Unplanned Radiation Dose Received From Image Guided Radiotherapy Procedures (MV CBCT and EPI) - Rolina K. Al-Wassia; Camelia Constantinescu (Journal of King Abdulaziz University: Medical Sciences, 2023)
To quantify and compare the doses to the tumor and the surrounding critical organs; a patients dose resulting from the orthogonal pair portal and megavoltage cone beam computerized tomography imaging techniques. Calculation based on a 6 MV Oncor linear accelerator equipped with an amorphous silicon flat panel, and done on Eclipse 3-D treatment planning system. 18 patients analyzed on three different treatment sites (head and neck, thorax, and pelvis). Data from 6 patients for each treatment site were used to calculate the mean doses. Calculations were done for: integral dose, patients maximum dose, dose at the isocenter, and mean dose to the tumor and each critical organ. The integral dose and isocenter dose per MU were higher for orthogonal pair technique than for megavoltage cone beam computerized tomography, for all treatment sites. For both techniques, the doses to the isocenter per MU were higher for head and neck and thorax than for the pelvis. Maximum dose difference to the patient showed greater variation for head and neck, but not for thorax and pelvis. The dose per MU to the tumor (GTV/CTV/PTV) or to the critical organs located closer and posterior to the tumor were diminutive for both techniques. The area covered by the 5cGy isodose line of the megavoltage cone beam computerized tomography technique was larger, including more volume of critical organs. The relatively high dose regions generated by megavoltage cone beam computerized tomography occur inside critical organs and tend to be larger than those generated by the orthogonal pair technique.